Predicting performance of fiber thermoelectric generator arrays in wearable electronic applications. (October 2020) - Zhang, Li-Sha; Yang, Bao; Lin, Shu-Pin; Hua, Tao; Tao, Xiao-Ming
Abstract: Emerging fiber-based thermoelectric generators have shown great potentials to power wearable electronics by harvesting thermal energy from human body and environment. However, the lack of quantitative analytical tools has hindered the research progress, particularly related to their design and evaluation, covering selection and optimization of thermoelectric, electric and structural materials, device structure, fabrication processes and application conditions. Here, we report a quantitative approach to predict the performance of three-dimensional fiber-based thermoelectric generators composed of one-dimensional fiber generator array, working under conductive and radiative heat transfer conditions with a low temperature difference. We first present an experimentally verified model of single fiber generator unit, consisting of core/sheath fiber leg and electrodes, to quantify the effects of the material properties and structural parameters on the output power and energy conversion efficiency of the fiber unit. Then we propose a second model of three-dimensional fiber-based thermoelectric array generator to predict its output performance in terms of fiber unit packing density and surface emissivity. Finally, the theoretical upper limits of output power and conversion efficiency are given for the fiber-based thermoelectric array generators worn on a human torso back under a range of ambient temperature. Graphical abstract: Image 1 Highlights: Models of three-dimensional array generator with a low temperature difference under conductive and radiative heat transfer. Quantified influences of materials, device structure and application conditions on output performance of the device. Theoretical upper limits of performance of the device worn on human back at various ambient temperatures.